Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Kedisiplinan SMK Annur - Ahmad Latip; Okpatrioka Okpatrioka (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research aims to find out about the implementation of human resource management in improving student discipline at Annur Depok Vocational School. The method used in this research is observation, interviews and documentation. The data analysis technique used is an interactive model and data triangulation to check the validity of the data. The results of the research show that Human Resource Management Implementation Planning is Improving student discipline at Annur Vocational School. In implementing Human Resources Management, the steps taken by Annur Vocational School begin with planning everything that will be done to improve the quality of education, such as recruitment and selection of teaching and education staff, then the planning is organized according to the school's needs. The next steps are the implementation of the plan that has been determined and direction, then supervision and evaluation are the final steps in implementing Human Resources Management related to the development of teacher professionalism and discipline in order to improve the quality of education. Implementation of Human Resources Management in an effort to improve discipline at Annur Vocational School.